Digital innovation in family firms: The roles of non-family managers and transgenerational control intentions - Anna Maria Bornhausen; Torsten Wulf (Small Business Economics, 2023)
Digital innovation, i.e. the creation of products and services, processes, or business models on the basis of digital technology, represents a new innovation phenomenon that offers important opportunities, but also entails high risks. Family firm research argues that family firms generally possess a greater ability to innovate, but differ in their willingness to do so. We propose that with regard to digital innovation family firms rather face an "ability and willingness challenge", i.e. they differ in their willingness and their ability to engage in digital innovation. We analyze two factors—non-family managers and transgenerational control intentions—that might help family firms overcome the ability and willingness challenge and that allows to explain heterogeneity among family firms in the adoption of digital innovation. An empirical, survey-based investigation of 104 German family firms supports our hypotheses. We contribute to the literature on digital innovation in family firms as well as on family firm professionalization.
Keywords: O32; 330; Family firm; Digital innovation; Transgenerational control intention; Loss aversion; Non-family management